2011
DOI: 10.1039/c1cy00150g
|View full text |Cite
|
Sign up to set email alerts
|

Design of hierarchical zeolite catalysts by desilication

Abstract: Hierarchical (or mesoporous) zeolites have received an ever-increasing attention due their improved performance in catalysed reactions with respect to conventional (purely microporous) zeolites. Desilication in alkaline media has become a widely applied preparation method to tailor these modified zeolites, due to an optimal combination of efficiency and simplicity. This Minireview presents recent developments that have expanded its general understanding and turned this top-down treatment highly versatile, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
472
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 611 publications
(487 citation statements)
references
References 69 publications
14
472
1
Order By: Relevance
“…It involves the selective extraction of silicon from the zeolite framework via treatment with diluted alkaline solutions at temperatures between 50 and 80 1C. 90,91 This method can be used to introduce intracrystalline mesopores with high degree of interconnectivity in zeolite crystals of different framework types. 36,[92][93][94][95][96] In contrast to dealumination, desilication does not significantly affect the acidity and the crystalline structure of zeolites.…”
Section: Demetalationmentioning
confidence: 99%
See 1 more Smart Citation
“…It involves the selective extraction of silicon from the zeolite framework via treatment with diluted alkaline solutions at temperatures between 50 and 80 1C. 90,91 This method can be used to introduce intracrystalline mesopores with high degree of interconnectivity in zeolite crystals of different framework types. 36,[92][93][94][95][96] In contrast to dealumination, desilication does not significantly affect the acidity and the crystalline structure of zeolites.…”
Section: Demetalationmentioning
confidence: 99%
“…The demetalation of pristine zeolite crystals has already been discussed in Section 3.4 and was found to be an efficient post-synthetic route for the preparation of hierarchical all-zeolite materials by removing parts of the zeolitic network. Moreover, Perez-Ramirez and co-workers 90,119 recently reported that this route can even be used as a 'postcompaction' treatment for the introduction of an additional pore system into already shaped zeolitic bodies (granules). Technically, the demetalation of already shaped zeolitic material has some advantages as compared to the demetalation of the initial fine zeolite powder, such as the easier handling of granular systems.…”
Section: Granular Zeolite Composites Via Compactionmentioning
confidence: 99%
“…[17] The hierarchical zeolites have shown enhanced catalytic performances with respect to the microporous analogues in diffusion-constrained reactions or those carried out in the liquid-phase at low temperatures. [11,18] In the present study, a post-synthetic desilication strategy in alkali media was followed to achieve hierarchical H-ZSM-5 ( Fig.1), starting from parent MFI zeolites with different Si/Al ratio. H-ZSM-5 is a wellknown microporous zeolite with a cross-section of straight channels (5.1 Å x 5.5 Å) intersected by zig-zag channels (5.3 Å x 5.6 Å) and it is widely used as a heterogeneous acid catalyst in a large number of reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Among the different synthetic procedures that can be followed to produce hierarchical zeolites, the top-down routes based on post-synthetic treatments in acid or alkali solutions are widely used, owing to favourable HSE (health-safety-environment) considerations and low production costs. [6,11,12] This method partially extracts the framework constituents (Al or Si) and depending on type of treatment, it can be classified into dealumination or desilication. In particular, under optimized conditions (acid or alkali sources, concentration, temperature and contact time), desilication in alkali media can be extensively used to create mesopores in zeolites, whilst preserving the crystalline structure almost entirely with a decreasing of the Si/Al ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The absence of a unified theory of heterogeneous catalysis has largely reflected difficulties in (i) synthesizing well defined, high surface area materials possessing a narrow distribution of coordination environments and oxidation states, and (ii) identifying the active surface species participating in the catalytic cycle. While advances in top-down [13][14][15][16] and bottom-up [17][18][19][20][21][22][23] engineering of nanocrystals and nanoporous solids are helping to address the former, a limited ability to directly observe surface reactions, coupled with reaction-induced restructuring, [24] has hampered past efforts to fingerprint and quantify structure-function relationships even in simple gas phase heterogeneously catalyzed processes such as CO [25,26] /alcohol oxidation [27] and alkene reduction. [28] This highlight paper illustrates how recent technical breakthroughs in X-ray photoelectron spectroscopy (XPS), X-ray absorption spectroscopy (XAS) and X-ray emission spectroscopy (XES), are enabling researchers to visualize catalytic processes under in situ or operando (true working) conditions, and use the resulting insight to nanoengineer improved heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%